Map of Trinidad, B.W.I. - (:unkn) unknown (Muir Marshall and Co.,[Trinidad and Tobago], 2011)
The postcard bears a small map of Trinidad.
Colour: Black and white; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Maps--Trinidad and Tobago; Trinidad and Tobago; Cartographic materials--Trinidad and Tobago